UNMANNED IMAGE NARRATION - Vp, Sangavi; Saleena, B (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Image analysis and understanding is used in various fields such as satellite imaging, robotic technologies, medical imaging, defense[G1]Â etc. Image analysisÂ is the process which involves extraction of meaningful information fromÂ images.Image annotation is the process of adding metadata to the image. The meaningful information is extracted based on the metadata available with the image. This research aims at understanding the input image and describing it to the user. The input image is segmented. The segments are annotated based on its properties like color, shapes in it. The segment annotations are collected and processed to get the overall meaning of the image. This research would improve image search, inform the user about the image even if the image is not displayed due to compatibility issues, and it is unmanned - no human assistance required to understand and display the image contents. [G2]Â [G3]Â Â